Productivity and quality of fodder sorghum hybrids S. Sioux and - Zvonimir Štafa; Darko Uher; Dubravko Maćešić; Zvonko Jantol; Stjepan Gal; Gordana Mužinić; Mladen Knežević; Marina Pavlak; Ana Pospišil (Mljekarstvo)
The objective of this study was to evaluate the yield and fodder quality of interpolated fodder sorghum as a second (additional) crop. The research was carried out on 4 family farms in lowland of northern Croatia between the Sava and Drava rivers. The area is densely populated, but the agricultural land is fragmented, unsuitably managed and utilized, and consists of different soil types. During the three-year trial carried out in different locations and conditions, the average green matter (GM) yield was 85.4 t ha-1 (73.0 – 93.3), while the dry matter (DM) yield was 14.11 t ha-1 (12.93-15.17). The mean crude fiber (CF) on DM concentration basis was 29.8 % (57.4 NDF, 28.8 % ADF and 13.8 % ADL), crude protein (CP) constituted 11.28 %, digestible crude protein (DCP) stood at 7.75 % and 6.38 MJ NEL. On average there were 1093 kg ha-1 DCP and 90.00 GJ NEL.